TANGGUNG JAWAB PEKERJA PADA PERJANJIAN KERJA ANTARA CV. KERABAT MAKMUR DENGAN PIHAK KEDUA DI PULAU RUPAT KABUPATEN BENGKALIS - Lestari, Wulan Ayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Broadly speaking, the order of Indonesian civil law provide the widest opportunity for the public to hold a mutual agreement about what is considered necessary for the purpose. However, the employment agreement often event of default that occurred between the two parties entered into an agreement. It therefore requires the responsibility of the party adverse to the injured party. As for the purpose of this thesis, namely: First, the responsibility of the workers on Cooperation Agreement CV. Kerabat Makmur to the second party in Rupat Bengkalis; Secondly, the rights and obligations in the implementation of the Cooperation Agreement CV.Kerabat Makmur to the second party in Rupat Bengkalis; Third, determine the settlement of disputes within the responsibility of the workers at the Cooperation Agreement CV. Kerabat Makmur to the second party in Rupat Bengkalis.This type of research is classified in this type of sociological research. Because in this study the authors directly conduct research at the locations under study in order to get a clear and complete picture of the problem studied, the study was conducted in Rupat Bengkalis. The data used are primary data, secondary data and data tertiary, data collection techniques using interview, and literature study.Problems arise in the months to three (3) the agreement was implemented, in which both parties can not complete the work by the agreed time. In Article 2 Employment Agreement. CV Kerabat Makmur said that the term held to carry out such work is five (5) months, but not until five (5) months of the second party can not complete the work contract and the members of the two run away without notice to the first party and the second party.Based on the results of research and discussion, the authors can menyimbulkan that: Firstly, the responsibility to do the second party to the CV. Kerabat Makmur while carrying out the work; Secondly, the rights and obligations specified in the Letter of Employment Agreement CV. Kerabat Makmur, but some of the rights and obligations of both parties are not met; Third, the dispute settlement is done by deliberation and consensus, but previously have been done subpoena. Suggestions, First, the CV. Kerabat Makmur provide additional working time again that the work can be completed with no hurry; Secondly, the CV. Kerabat Makmur and the second party should conduct rigorous oversight to field more often, so it can know things and events that occur in the labor market; Third, the settlement of a dispute on the CV. Kerabat Makmur should be decisive action from the first party to give a warning.Keywords: Responsibility, Employment Agreement